Identification of bovine Eimeria species pathogenic using PCR ITS-1 in Indonesia - RADEN WISNU NURCAHYO; FITRINE EKAWASTI; LINTANG WINANTYA FIRDAUSY; VIKA ICHSANIA NINDITYA; MUKH FAJAR NASRULLOH; DYAH AYU KURNIAWATI; FATHUR ROHMAN HARYADI; JOKO PRASTOWO; DWI PRIYOWIDODO (Society for Indonesian Biodiversity, 2023)
Abstract. Nurcahyo RW, Ekaswasti F, Firdausy LW, Ninditya VI, Nasrulloh MF, Kurniawati DA, Haryadi FR, Prastowo J, Priyowidodo D. 2023. Identification of bovine Eimeria species pathogenic using PCR ITS-1 in Indonesia. Biodiversitas 24: 4684-4689. Bovine eimeriosis is one of Indonesia's cattle's most significant health issues caused by the intestinal protozoan parasite Eimeria spp. Eimeria spp., E. zuernii, E. alabamensis, E. aburnensis, and E. bovis are recognized as most pathogenic since they cause clinical symptoms. This study aimed to identify pathogenic Eimeria spp. and explore their evolutionary relationships using the molecular marker, the internal transcribed spacer-1 (ITS-1). A total of 171 fecal samples were collected from the provinces of Banten, Lampung, and West Java, and 43 (25.1%) were infected with oocysts of Eimeria spp. by microscopic examination. The positive samples were further confirmed for different Eimeria species by amplifying and sequencing the ITS-1 gene. After editing and alignment, the sequences were considered for analyses, and the phylogenetic analysis confirmed four species of Eimeria such as E. bovis 39 (22.8%), E. zuernii 23 (13.5%), E. alabamensis 7 (4.09%), and E. aburnensis 25 (14.6%). In this study, several Eimeria species were related to overseas species; therefore, additional risk analysis is needed to control the spread of bovine eimeriosis. It is possible to learn important details regarding the ecology and population genetics of Eimeria spp. by employing sequencing and phylogenetic analysis to categorize all positive samples of the eimeriosis as pathogenic Eimeria spp.